Inhibition of lipid peroxidation and protein oxidation in rat liver mitochondria by curcumin and its analogues - Wei, Qing-Yi; Chen, Wei-Feng; Zhou, Bo; Yang, Li; Liu, Zhong-Li (Biochimica et biophysica acta, 2006)
Curcumin (1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione, 1) is a yellow ingredient isolated from turmeric ( curcumin longa). It has been shown to exhibit a variety of biological activities including antioxidative activity. In order to find more active antioxidants with 1 as the lead compound we synthesized curcumin analogues, i.e., 1-(3,4-dihydroxyphenyl)-7-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione ( 2), 1-(4-hydroxy-3-methoxyphenyl)-7-(4-hydroxyphenyl)-1,6-heptadiene-3,5-dione ( 3), 1,7-bis-(4-hydroxyphenyl)-1,6-heptadiene-3,5-dione ( 4), 1-(3,4-dimethoxyphenyl)-7-(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione ( 5), 1,7-bis(3,4-dimethoxyphenyl)-1,6-heptadiene-3,5-dione ( 6), and 1,7-diphenyl-1,6-heptadiene-3,5-dione ( 7), and evaluated their antioxidative activity. The in vitro oxidative damage to both lipids and proteins in rat liver mitochondria was used as a model to study the free radical-induced oxidative damage of biological lipids as well as proteins and the protective effects of these curcumin analogues. It was found that these compounds, except 6 and 7, could effectively inhibit the free radical induced lipid peroxidation and protein oxidative damage of rat liver mitochondria by H-atom abstraction from the phenolic groups. Compound 2 which bear ortho-diphenoxyl functionality exhibited remarkably higher antioxidative activity for lipids and proteins than curcumin and other analogues, and the 4-hydroxy-3-methoxyphenyl group also play an important role in the antioxidative activity.